The King James New Testament: How a Translation Determined Christian Thought on Marriage and Celibacy for Nearly Four Hundred Years - Omanson, Roger L. (The Bible translator, 2013)
Traditional translations of 1 Corinthians 7.1 suggest to the reader that the words “It is good for a man not to touch a woman” (KJV) are Paul’s words of advice to the Corinthians. Many recent translations, however, correctly indicate that Paul is here quoting words from a letter written to him from the Corinthians. The Greek words peri de (“now concerning”) here and in 8.1; 12.1; 16.1, and 16.12 introduce a new topic that has been raised in a letter from Corinth. The words translated “to touch” are a euphemism for “to have sexual relations.” The following translation in REB is recommended as a model for other languages: “Now for the matters you wrote about. You say, ‘It is a good thing for a man not to have intercourse with a woman.’”